A case of a co-secreting TSH and growth hormone pituitary adenoma presenting with a thyroid nodule. (23rd August 2018) - Adams, Laura Hamilton; Adams, Derick
Summary: Co-secreting TSH and growth hormone pituitary adenomas are rare. We present a case of a 55-year-old woman who presented with symptoms of neck fullness. Ultrasound revealed multiple thyroid nodules and examination revealed several clinical features of acromegaly. She was found to have a co-secreting TSH and growth hormone pituitary macroadenoma. She underwent surgical resection followed by gamma knife radiation, which resulted in complete remission of her TSH and GH-secreting adenoma. Learning points: TSH-secreting pituitary adenomas are rare and about one-third co-secrete other hormones. Thyroid nodules are common in acromegaly and can be the presenting sign of a growth hormone-secreting pituitary adenoma. In the workup of acromegaly, assessment of other pituitary hormones is essential, even in the absence of symptoms of other pituitary hormone dysfunction. Complete remission of co-secreting GH and TSH pituitary macroadenomas is possible with surgery and radiation alone.